Usaha Tiram Di Kelurahan Coppo Kecamatan Barru Kabupaten Barru - Ulfah, Marya (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study is to find out: (1) An overview of traditional traders' income before the Grand Mall, (2) a description of the income of traditional traders after their Grand Mall, (3) The impact of the Grand Mall on the income of traditional market traders. The method used is descriptive quantitative and the population in this study are traditional traders who sell goods Related to the 288 merchants sold at the Grand Mall. The sample is 72 traders. Data collection techniques with observation, interviews, questionnaires / questionnaires and documentation with relevant parties. Data analysis method uses descriptive analysis. The results showed that the Grand Mall research influenced traditional market traders. Decreasing number, Decreasing the number of sales, Decreasing the number of sales of goods. Based on 72 traders only 23 agreed and 49 traditional traders were not approved by the modern market. Grand Mall is not as strong as its influence on the income of traditional market traders only increasing 23 traders from 72 traditional traders as a sample, or around 32%.